2012
DOI: 10.1039/c2sm06969e
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial biomimetic hybrid films

Abstract: In this work, we present a novel method to prepare a hybrid coating based on dextran grafted to a substrate and embedded with silver nanoparticles (Ag NPs). First, the Ag NPs are synthesized in situ in the presence of oxidized dextran in solution. Second, the oxidized dextran is exposed to an amine functionalized surface resulting in the simultaneous grafting of dextran and the trapping of Ag NPs within the layer. The NP loading is controlled by the concentration of silver nitrate, which is 2 mM (DEX-Ag2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In previous work, we demonstrated that oxidized dextran, i.e., aldehyde and hydroxyl groups, could reduce silver cations and stabilize the resulting Ag NPs in aqueous solution (Ferrer, Hickok 2012). Another hydroxyl based polysaccharide, starch, has also been employed to reduce Ag NPs in solution (Vigneshwaran 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we demonstrated that oxidized dextran, i.e., aldehyde and hydroxyl groups, could reduce silver cations and stabilize the resulting Ag NPs in aqueous solution (Ferrer, Hickok 2012). Another hydroxyl based polysaccharide, starch, has also been employed to reduce Ag NPs in solution (Vigneshwaran 2006).…”
Section: Resultsmentioning
confidence: 99%
“…However, the comparison between different systems is not straightforward because the position, shape and intensity of the SPR depends on the dielectric constant of the particle and medium, the electronic interactions between the stabilizer and NPs, and the size, shape and the size dispersity [24]. For instance, Ag NPs (~ 5 nm) prepared in situ in dextran solution exhibit a SPR at 412 nm [7] whereas Ag NPs having similar size but prepared in situ in a NG1:1 solution exhibit a peak absorption at 430 nm. Furthermore, a blue shift of the SPR is expected as particle size decreases, whereas the results in Figure 3 showed a slight red shift.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of NGs was carried out as previously described, via a Maillard heating reaction followed by heat-gelation at 80 °C [7]. This methodology leads to core-shell type NG with a lysozyme-rich core and a dextran-rich shell [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations